Influência do número de refundições da liga Ni-Cr-Mo-Ti sobre as propriedades de próteses metalocerâmicas - Vilar, Caroline Dantas (2008)
A frequently encountered difficulty in oral prosthetics is associated with the loss of metallic alloys during the melting stage of the production of metal-ceramic replacement systems. Remelting such materials could impar their use in oral rehabilitation due to loss in esthetics, as well as in the chemical, physical, electrochemical and mechanical properties. Nowadays, the Ni-Cr-Mo-Ti alloy is widely used in metal-ceramic systems. Manufacturers state that this material can be remelted without significant alterations in its behavior, however little has been established as to the changes in the performance of this alloy after successive remelting, which is common practice in oral prosthetics. Therefore, the objective of this study was to evaluate possible changes in the esthetics and associated properties of metalceramic samples consisting of Ni-Cr-Mo-Ti and dental porcelain. Three to five remelting steps were carried out. The results revealed that Ni-Cr-Mo-Ti can be safely used even after three remelting steps. Further remelting significantly affect the characteristics of the alloys and should not be recommended for the manufacture of metal-ceramic systems